Endless belt for electrophotographic apparatus
By using a resin composition of polyamide imide resin and an organic phosphorus compound as the base layer, the shortcomings in the existing annular belt in terms of physical properties, flame retardancy, cost and environmental load are solved, and an efficient, environmentally friendly and economical annular belt for electrophotographic equipment is achieved.
Patent Information
- Application Number
- CN202411412524.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-30
- Filing Date
- 2024-10-11
- Publication Date
- 2025-05-02
AI Technical Summary
The existing annular belts for electrophotographic equipment have shortcomings in taking into account both physical properties and flame retardant, low cost and environmental load. The annular belt of fluororesin has good flame retardant properties but low elastic modulus and expensive materials. The annular belt of polyimide resin has high flame retardant properties and elastic modulus but has high materials and poor productivity. The annular belt of polyimide resin has low cost but difficult to take into account both flame retardant properties and physical properties.
The resin composition containing a polyamide imide resin and a flame retardant is used as the base layer. The polyamide imide resin is derived from the acid anhydride of diphenylmethane diisocyanate, dimethylbiphenyldiisocyanate and aromatic polycarboxylic acid. The flame retardant is an organic phosphorus compound, with a molar ratio ranging from 95/5 to 30/70 and a flame retardant content within the range of 1.0 to 10 parts by mass per 100 parts by mass of the polyamide imide resin.
The annular belt for electrophotographic equipment that takes into account both physical properties and flame retardant properties, is low-cost and takes into account environmental load. The flame retardant is not easy to seep out, and the idle rotation of the annular belt is suppressed. The synthesis time of the polyamide imide resin is short, and the cost is favorable, and the organophosphorus compound has low toxicity and good environmental protection.
Smart Images

Figure CN119912812A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an endless belt for an electrophotographic device, and more particularly, to an endless belt for an electrophotographic device used as a conveyor belt, an intermediate transfer belt, etc. in an electrophotographic device such as a full-color LBP (laser beam printer) and a full-color MFP (multi-function printer) that adopts electrophotographic technology. Background Art
[0002] As endless belts such as conveyor belts and intermediate transfer belts of electrophotographic equipment, there are known endless belts having a base layer using a fluorine-based resin, a polyimide resin, or a polyamide-imide resin.
[0003] Prior art literature Patent Literature Patent Document 1: Japanese Patent Application Publication No. 2006-047587. Summary of the invention
[0004] Problems to be solved by the invention The endless belt of fluororesin can ensure flame retardancy, but the elastic modulus is low and the material is expensive. Furthermore, there is also the problem of environmental load. The endless belt of polyimide resin can ensure flame retardancy and has a high elastic modulus, but the material is expensive, and the manufacturing also requires high temperature and a long time, which has poor productivity and is disadvantageous in terms of cost. The endless belt of polyamide-imide resin is easy to ensure a high elastic modulus, is cheaper than polyimide resin, and is manufactured at low temperature and in a short time, which is advantageous in terms of cost, but the material monomer is difficult to ensure flame retardancy, and a flame retardant needs to be added, and the balance between physical properties and flame retardancy becomes a problem.
[0005] The problem to be solved by the present invention is to provide an endless belt for an electrophotographic device which has both good physical properties and flame retardancy, is low-cost and can take environmental load into consideration.
[0006] Means used to solve problems In order to solve the above-mentioned problems, the endless belt for an electrophotographic device according to the present invention is an endless belt for an electrophotographic device having at least a base layer, wherein the base layer is formed using a resin composition containing a polyamide-imide resin and a flame retardant, the polyamide-imide resin has a structural unit derived from the following (A) to (C), the molar ratio of the structural unit (α) derived from the (A) to the structural unit (β) derived from the (B) is in the range of (α) / (β)=95 / 5~30 / 70, and the flame retardant is an organic phosphorus compound. (A) diphenylmethane diisocyanate (MDI), (B) dimethyl diphenyl diisocyanate (TODI), (C) Anhydrides of aromatic polycarboxylic acids.
[0007] Preferably, the organic phosphorus compound is an organic phosphorus compound with a molecular weight of 350 or more. Preferably, the anhydride of the aromatic polycarboxylic acid (C) is trimellitic anhydride. Preferably, the organic phosphorus compound is a phosphate ester. Preferably, the content of the organic phosphorus compound is 1.0 mass part or more and 10 mass parts or less relative to 100 mass parts of the polyamide-imide resin.
[0008] (1) The endless belt for an electrophotographic device according to the present invention is an endless belt for an electrophotographic device comprising at least a base layer, wherein the base layer is formed using a resin composition comprising a polyamideimide resin and a flame retardant, the polyamideimide resin has a structural unit derived from the following (A) to (C), the molar ratio of the structural unit (α) derived from the (A) to the structural unit (β) derived from the (B) is in the range of (α) / (β)=95 / 5 to 30 / 70, and the flame retardant is an organic phosphorus compound. (A) diphenylmethane diisocyanate (MDI), (B) dimethyl diphenyl diisocyanate (TODI), (C) Anhydrides of aromatic polycarboxylic acids.
[0009] (2) Preferably, in the above (1), the organic phosphorus compound is an organic phosphorus compound having a molecular weight of 350 or more.
[0010] (3) Preferably, in the above (1) or (2), the anhydride of the aromatic polycarboxylic acid (C) is trimellitic anhydride.
[0011] (4) Preferably, in any one of (1) to (3) above, the organic phosphorus compound is a phosphate ester.
[0012] (5) Preferably, in any one of the above (1) to (4), the content of the organic phosphorus compound is 1.0 part by mass or more and 10 parts by mass or less relative to 100 parts by mass of the polyamide-imide resin.
[0013] Effects of the Invention According to the endless belt for an electrophotographic device involved in the present invention, the base layer is formed using a resin composition containing a polyamide-imide resin and a flame retardant, the polyamide-imide resin has structural units derived from the above-mentioned (A) to (C), and the molar ratio of the structural unit (α) derived from the above-mentioned (A) to the structural unit (β) derived from the above-mentioned (B) is in the range of (α) / (β)=95 / 5~30 / 70, and the flame retardant is an organic phosphorus compound, so that both physical properties and flame retardancy can be taken into account, low cost can be achieved, and environmental load can be considered.
[0014] When the organic phosphorus compound has a molecular weight of 350 or more, it is less likely to ooze out to the surface of the base layer, and it is easy to suppress idle running of the endless belt due to a decrease in the friction coefficient.
[0015] When the anhydride of the aromatic polycarboxylic acid (C) is trimellitic anhydride, it has high reactivity with the (A) and the (B) and can be produced at a low temperature and in a short time, which is advantageous in terms of cost.
[0016] Furthermore, when the organic phosphorus compound is a phosphate ester, a small amount of addition can exhibit an excellent flame retardant effect, so it is easy to suppress the degradation of physical properties. In addition, since the toxicity is low, the environmental load can be further considered.
[0017] Furthermore, when the content of the organic phosphorus compound is 1.0 part by mass or more and 10 parts by mass or less based on 100 parts by mass of the polyamide-imide resin, even a small amount of addition can exhibit an excellent flame retardant effect, and degradation of physical properties can be further suppressed. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a perspective view schematically showing an endless belt for an electrophotographic device according to one embodiment of the present invention.
[0019] Figure 2 yes Figure 1 A cross-sectional view of an endless belt for an electrophotographic apparatus is shown.
[0020] Description of Reference Numerals 10: Annular belt; 12: Grassroots; 14: Surface. DETAILED DESCRIPTION
[0021] The endless belt for an electrophotographic apparatus (hereinafter, sometimes simply referred to as an endless belt) according to the present invention will be described in detail.
[0022] Figure 1 An endless belt according to one embodiment of the present invention is shown. Figure 2 express Figure 1 A cross-sectional view of the annular belt is shown.
[0023] The endless belt 10 includes a cylindrical base layer 12 and a surface layer 14 formed on the outer peripheral surface of the base layer 12 .
[0024] The base layer 12 serves as a base material of the endless belt 10. The base layer 12 is formed in a cylindrical shape and has a seamless structure without any joint in the circumferential direction.
[0025] The base layer 12 is formed using a resin composition containing a polyamide-imide resin (PAI) having structural units derived from the following (A) to (C) and a flame retardant.
[0026] (A) Methylene diphenyl diisocyanate (MDI) (B) Tolyldiisocyanate (TODI) (C) Anhydrides of aromatic polycarboxylic acids Examples of the diphenylmethane diisocyanate (MDI) of (A) include 4,4′-diphenylmethane diisocyanate, 2,4′-diphenylmethane diisocyanate, polymeric MDI, etc. These can be used alone or in combination of two or more.
[0027] The molar ratio of the structural unit (α) derived from MDI to the structural unit (β) derived from TODI needs to be set in the range of (α) / (β)=95 / 5~30 / 70. It is preferably (α) / (β)=80 / 20~35 / 65, and more preferably in the range of (α) / (β)=70 / 30~40 / 60. If the molar ratio of the structural unit (α) is greater than 95 (the molar ratio of the structural unit (β) is less than 5), the tensile modulus is low and the creep property is poor. In addition, the manufacturing also takes a long time, the productivity is poor, and it is disadvantageous in terms of cost. Moreover, if the molar ratio of the structural unit (α) is less than 30 (the molar ratio of the structural unit (β) is greater than 30), cracks are easily generated and the folding resistance (crack resistance) deteriorates.
[0028] (C) Using an anhydride of an aromatic polycarboxylic acid. If an aromatic polycarboxylic acid is used instead of an anhydride, the number of amide bonds increases, the elastic modulus decreases, and dimensional changes due to water absorption occur. In addition, the synthesis time becomes longer, which is also disadvantageous in terms of cost. If an anhydride of an aliphatic polycarboxylic acid is used instead of an aromatic one, the elastic modulus decreases.
[0029] The anhydride of the aromatic polycarboxylic acid (C) is not particularly limited as long as it is a substance that undergoes a condensation reaction with the above-mentioned MDI and the above-mentioned TODI and has an aromatic ring. For example, in addition to the anhydride of trimellitic acid and naphthalene-1,2,4-tricarboxylic acid, there can be mentioned benzene-1,2,4,5-tetracarboxylic acid (pyromellitic acid), benzophenone-3,3',4,4'-tetracarboxylic acid, diphenyl ether-3,3',4,4'-tetracarboxylic acid, benzene-1,2,3,4-tetracarboxylic acid, biphenyl-3,3',4,4'-tetracarboxylic acid, biphenyl-2,2',3,3'-tetracarboxylic acid, naphthalene-2,3,6,7-tetracarboxylic acid, naphthalene-1,2,4,5-tetracarboxylic acid, naphthalene-1,4,5,8-tetracarboxylic acid, decahydronaphthalene-1,4,5,8-tetracarboxylic acid, 4,8-dimethyl-1,2,3,5,6, 7-hexahydronaphthalene-1,2,5,6-tetracarboxylic acid, 2,6-dichloronaphthalene-1,4,5,8-tetracarboxylic acid, 2,7-dichloronaphthalene-1,4,5,8-tetracarboxylic acid, 2,3,6,7-tetrachloronaphthalene-1,4,5,8-tetracarboxylic acid, phenanthrene-1,3,9,10-tetracarboxylic acid, perylene-3,4,9,10-tetracarboxylic acid, bis(2,3-dicarboxyphenyl)methane, bis(3,4-dicarboxyphenyl) ) methane, 1,1-bis(2,3-dicarboxyphenyl)ethane, 1,1-bis(3,4-dicarboxyphenyl)ethane, 2,2-bis(2,3-dicarboxyphenyl)propane, 2,3-bis(3,4-dicarboxyphenyl)propane, bis(3,4-dicarboxyphenyl)sulfone, bis(3,4-dicarboxyphenyl)ether, ethylene glycol bis(anhydrotrimellitate), propylene glycol bis(anhydrotrimellitate) and other dianhydrides. These may be used alone or in combination of two or more. Among them, the anhydride of trimellitic acid (trimellitic anhydride) is preferably used in terms of reactivity, cost, solubility and the like.
[0030] The number average molecular weight (Mn) of the polyamideimide resin is preferably in the range of 10,000 to 50,000, and particularly preferably in the range of 15,000 to 40,000. This is because if the Mn of the polyamideimide resin is less than 10,000, the tear strength becomes low and the durability becomes poor, and if the Mn of the polyamideimide resin is greater than 50,000, the solution viscosity becomes high and the processability tends to become poor.
[0031] The polyamide-imide resin can be prepared, for example, as follows. That is, a reaction container equipped with a stirrer, a nitrogen inlet pipe, a thermometer, and a cooling pipe is prepared, MDI and TODI are mixed in a predetermined molar ratio, and a predetermined amount of an acid component such as trimellitic anhydride is mixed, and a polar solvent such as N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC), γ-butyrolactone is added, and the temperature is raised to a predetermined temperature (preferably 130° C.) for a predetermined time (preferably 1 hour) under a nitrogen flow while stirring, and the reaction is stopped after reacting at the predetermined temperature (preferably 130° C.) for a predetermined time (preferably about 5 hours), thereby preparing a solvent for the polyamide-imide resin.
[0032] The flame retardant used together with the polyamide-imide resin is preferably an organic phosphorus compound. Even if the organic phosphorus compound is added in a small amount, it can show an excellent flame retardant effect, so it can suppress the generation of cracks caused by a large amount of addition, the deterioration of folding resistance (crack resistance), and it is easy to suppress the reduction of physical properties. In addition, due to the low toxicity, the environmental load can be further considered. Organic phosphorus compounds with large molecular weight are not easy to seep out to the surface of the base layer 12, and are more preferred. The molecular weight of the organic phosphorus compound is preferably 350 or more. More preferably, it is 360 or more, and more preferably, it is 370 or more. The upper limit of the molecular weight of the organic phosphorus compound is not particularly limited, and from the viewpoints of compatibility with the polyamide-imide resin, solvent solubility, etc., it is preferably 1000 or less. More preferably, it is 750 or less, and more preferably, it is 500 or less.
[0033] As the organophosphorus compound, phosphoric acid esters, phosphazene compounds, etc. can be cited. Among them, phosphoric acid esters and phosphazene compounds are more preferred from the viewpoints of compatibility with polyamide-imide resins, versatility, and supplyability. In addition, phosphoric acid esters are particularly preferred from the viewpoints of excellent flame retardant effects and low toxicity when added in small amounts.
[0034] Phosphate esters include aromatic phosphate esters, condensed phosphate esters, and the like. Phosphate esters are preferably aromatic phosphate esters from the viewpoint of high flame retardant effect. Phosphate esters having one or more aromatic groups are included as aromatic phosphate esters. Phosphate esters having aromatic phosphate groups are more preferably phosphate esters in which each ester group has an aromatic group (having three aromatic groups) from the viewpoint of flame retardant effect. The aromatic groups of the phosphate ester having multiple aromatic groups may be identical to each other or may be one or more different aromatic groups.
[0035] Examples of the aromatic phosphate include triphenyl phosphate, tricresyl phosphate, tricresyl phosphate, triisopropylphenyl phosphate, tritert-butylphenyl phosphate, cresyl diphenyl phosphate, cresyl ditert-butylphenyl diphenyl phosphate, bistert-butylphenyl phosphate, isopropylphenyl diphenyl phosphate, bis(isopropylphenyl) diphenyl phosphate, and 2-ethylhexyl diphenyl phosphate. Among them, tricresyl phosphate and cresyl ditert-butylphenyl phosphate are more preferred from the viewpoint of being less likely to ooze out onto the surface of the base layer 12.
[0036] Examples of the condensed phosphoric acid ester include resorcinol bis-diphenyl phosphate, resorcinol bis-di(xylyl) phosphate, bisphenol A bis-diphenyl phosphate, and biphenyl bis-diphenyl phosphate.
[0037] Examples of the phosphazene compound include phenoxyphosphazenes, (poly)tolyloxyphosphazenes (e.g., o-tolyloxyphosphazenes, m-tolyloxyphosphazenes, p-tolyloxyphosphazenes, o-m-tolyloxyphosphazenes, o-p-tolyloxyphosphazenes, m-p-tolyloxyphosphazenes, o-m-p-tolyloxyphosphazenes, etc.), cyclic and / or chain C1-6 alkyl C6-20 aryloxyphosphazenes such as (poly)xylyloxyphosphazenes, (poly)phenoxytolyloxyphosphazenes (e.g., phenoxy-o-tolyloxyphosphazenes, phenoxy-m-tolyloxyphosphazenes, phenoxy-p-tolyloxyphosphazenes, phenoxy-o-m-tolyloxyphosphazenes, phenoxy-o-p-tolyloxyphosphazenes, phenoxy-m-p-tolyloxyphosphazenes, phenoxy-o-m-p-tolyloxyphosphazenes, etc.), (poly)phenoxyxylyloxyphosphazenes, (poly)phenoxytolyloxyxylyloxyphosphazenes, and cyclic and / or chain C6-20 aryl C1-10 alkyl C6-20 aryloxyphosphazenes such as (poly)phenoxytolyloxyxylyloxyphosphazenes.
[0038] Among them, cyclic and / or chain phenoxyphosphazenes, cyclic and / or chain C1-3 alkyl C6-20 aryloxyphosphazenes, and C6-20 aryloxy C1-3 alkyl C6-20 aryloxyphosphazenes (for example, cyclic and / or chain tolyloxyphosphazenes, cyclic and / or chain phenoxytolylphenoxyphosphazenes, etc.) are preferred.
[0039] The content of the organic phosphorus compound as a flame retardant is preferably 1.0 mass parts or more and 10 mass parts or less relative to 100 mass parts of polyamide-imide resin. When the above content is 1.0 mass parts or more, it is possible to exert an excellent flame retardant effect. In addition, from this viewpoint, the above content is more preferably 2.0 mass parts or more, and more preferably 2.5 mass parts or more. On the other hand, when the above content is 10 mass parts or less, it is suppressed to be added in small amounts, and it is easy to suppress the reduction of physical properties. In addition, from this viewpoint, the above content is more preferably 7.0 mass parts or less, and more preferably 5.0 mass parts or less.
[0040] In the resin composition forming the base layer 12 , a conductive filler may be used in addition to the polyamide-imide resin and the flame retardant.
[0041] As the conductive filler, there can be mentioned conductive carbon powders such as carbon black and graphite, metal powders such as aluminum powder and stainless steel powder, conductive metal oxides such as conductive zinc oxide (c-ZnO), conductive titanium oxide (c-TiO2), conductive iron oxide (c-Fe3O4), and conductive tin oxide (c-SnO2), ionic conductive agents such as quaternary ammonium salts, sulfonates, aliphatic polyols, and aliphatic alcohol sulfates, etc. These can be used alone or in combination of two or more.
[0042] The resin composition for forming the base layer 12 may contain an organic solvent such as DMF, DMAC, toluene, acetone, and NMP, and a filler, as necessary, together with the above-mentioned components.
[0043] The resin composition forming the base layer 12 can be prepared by, for example, appropriately blending a polyamide-imide resin, a flame retardant, an organic solvent, and a filler as required, mixing with a stirring blade, and then dispersing the mixture using a ring mill, a ball mill, a sand mill, or the like.
[0044] Next, the material for forming the surface layer 14 formed on the peripheral surface of the base layer 12 is not particularly limited, and for example, silicone resins, fluorine resins, polyurethane resins, acrylic resins, polyamide resins, etc. can be listed. They can be used alone or in combination of two or more. Among them, usually considering the workability, it is preferred to use a liquid or solvent-soluble type. In addition, for the purpose of preventing pollution, improving the strength or adhesion of the coating film, a resin obtained by modifying the resin material can be used, for example, a modified acrylic resin can be listed. As the modified acrylic resin, as long as it is a resin obtained by modifying the molecular structure of acrylic resin as a matrix and utilizing other resins or resin components, it is not particularly limited, and silicone-modified acrylic resin is preferably used.
[0045] Examples of the silicone-modified acrylic resin include silicone-grafted acrylic resins. The silicone-grafted acrylic resin is not particularly limited as long as it is a resin obtained by graft-polymerizing a silicone resin onto an acrylic resin (main chain). Specific examples of the silicone-grafted acrylic resin include SYMAC US-350 manufactured by Toagosei Co., Ltd.
[0046] In addition, as the above-mentioned surface layer material, a material obtained by cross-linking the resin material using a resin cross-linking agent such as isocyanate resin, amino resin, phenolic resin, xylene resin, or an ultraviolet curing material obtained by mixing a photopolymerization initiator into a photosensitive monomer or polymer can also be used.
[0047] The surface layer material can be prepared by, for example, appropriately coordinating modified acrylic resin and organic solvents such as DMF, toluene, and acetone, and mixing with stirring blades. In addition, in order to form each layer with good precision, the organic solvent used in the formation material of the adjacent layer is preferably an organic solvent of a different type from each other. That is, the organic solvent used in the surface layer material and the organic solvent used in the base layer material are preferably an organic solvent of a different type from each other.
[0048] The endless belt 10 can be made, for example, as follows. First, a resin composition forming a base layer 12 is sprayed on the surface of a mold (cylindrical substrate). Then, it is dried at 150 to 300° C. for 3 to 6 hours, thereby forming a base layer 12 on the surface of the mold. Next, a surface layer material is applied to the surface of the base layer 12 by an immersion method and dried, and air is blown between the base layer 12 and the cylindrical substrate, thereby extracting the cylindrical substrate, and an endless belt 10 having a two-layer structure in which a surface layer 14 is formed on the surface of the base layer 12 can be made. In addition, the method for forming the surface layer 14 is not limited to the above-mentioned immersion method, and can also be formed by spraying in the same way as the method for forming the base layer 12.
[0049] The base layer 12 of the endless belt 10 can be made by extrusion molding, inflation molding, blow molding, dipping, centrifugal molding, etc. in addition to the above-mentioned manufacturing method. And, by omitting the formation of the surface layer 14, an endless belt of a single-layer structure consisting only of the base layer 12 can be made.
[0050] The thickness of each layer of the endless belt 10 is appropriately set according to the purpose of the belt, and the thickness of the base layer 12 is usually in the range of 30 to 300 μm, preferably in the range of 50 to 200 μm. In addition, the thickness of the surface layer 14 is preferably in the range of 0.1 to 10 μm, and particularly preferably in the range of 0.5 to 5 μm. In addition, the endless belt 10 preferably has an inner circumference of 90 to 1500 mm and a width of about 100 to 500 mm. That is, if it is set within the range of the above-mentioned size, it is formed into a size suitable for assembly into an electronic photographic copier, etc.
[0051] According to the endless belt 10 constructed as above, the base layer 12 is formed using a resin composition comprising a polyamide-imide resin and a flame retardant, wherein the polyamide-imide resin has structural units derived from the above-mentioned (A) to (C), and the molar ratio of the structural unit (α) derived from (A) to the structural unit (β) derived from (B) is in the range of (α) / (β)=95 / 5~30 / 70, and the flame retardant is an organic phosphorus compound, so that both physical properties and flame retardancy are taken into account, low cost is achieved and environmental load can be taken into account.
[0052] The endless belt for an electrophotographic device of the present invention may be any structure as long as it has at least a base layer, and is not limited to Figure 1 As shown in the figure, the surface layer 14 is directly formed on the outer peripheral surface of the base layer 12. The endless belt for the electrophotographic device of the present invention may also be, for example, a single-layer structure consisting of only the base layer, a three-layer structure in which a thermoplastic resin layer or a rubber elastic layer is sandwiched between the base layer and the surface layer, or a four-layer structure in which both a thermoplastic resin layer and a rubber elastic layer are sandwiched between the base layer and the surface layer.
[0053] The material for the thermoplastic resin layer interposed between the base layer and the surface layer is not particularly limited, and a solvent such as methyl ethyl ketone (MEK) or toluene may be used together with the thermoplastic resin as needed. The thermoplastic resin layer material may also contain a conductive filler as described above.
[0054] In addition, the thermoplastic resin is not particularly limited, and examples thereof include fluorine resins such as polyvinylidene fluoride (PVDF), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), ethylene-tetrafluoroethylene copolymer (ETFE), polyethylene resins, polystyrene resins, acrylic resins, polycarbonate (PC) resins, polyamide resins, EVA (ethylene-vinyl acetate copolymer) resins, EEA (ethylene-ethyl acrylate copolymer) resins, etc. These resins can be used alone or in combination of two or more. Among them, fluorine resins such as PVDF are preferably used from the perspective of excellent flame retardancy.
[0055] In addition, as the rubber elastic layer material between the base layer and the surface layer, a vulcanization accelerator, a solvent, a processing aid, an anti-aging agent, etc. may be used as needed together with the rubber material and the vulcanizing agent. In addition, the rubber elastic layer material may also be blended with the above-mentioned conductive filler.
[0056] The rubber material is not particularly limited, and from the viewpoint of flame retardancy, chlorinated polyethylene rubber (CPE), chloroprene rubber (CR), etc. can be used. Among them, the best material is selected according to the electrical characteristics, elasticity, and durability required of each intermediate transfer belt.
[0057] The endless belt for electronic photographic equipment of the present invention is suitable for use in transfer of colorant images, paper transfer and transportation, photosensitive body substrate and the like in electronic photographic equipment adopting electronic photographic technology such as full-color LBP (laser beam printer) and full-color MFP (multifunction printer), but is not limited to these. For example, it can also be used as a transfer belt of a non-full-color monochrome electronic photographic copier.
[0058] Example Hereinafter, the present invention will be described in detail using Examples and Comparative Examples. The present invention is not limited to the following Examples.
[0059] (Example 1) <Preparation of base layer forming material> In a reaction vessel equipped with a stirrer, a nitrogen inlet pipe, a thermometer, and a cooling pipe, 54.0 parts by mass of MDI, 3.0 parts by mass of TODI, 43.0 parts by mass of trimellitic anhydride, and 280 parts by mass of NMP solvent were added, and the temperature was raised to 130°C over 1 hour while stirring under a nitrogen flow, and the reaction was kept at 130°C for about 5 hours, and then the reaction was stopped to prepare a PAI-NMP solution. 3.0 parts by mass of a flame retardant were added to the prepared PAI-NMP solution. <1> , 5 parts by mass of conductive carbon were mixed using a stirring blade and then dispersed in a ball mill to prepare a base layer forming material.
[0060] <Manufacturing of Endless Belt> A mold (cylindrical substrate) was prepared, a base layer forming material was sprayed on its surface, a base layer was formed on the surface of the mold, and a heat treatment was performed at 250°C for 2 hours. Next, air was blown between the base layer and the cylindrical substrate, and the cylindrical substrate was pulled out to produce an endless belt with a single-layer structure having a thickness of 80 μm.
[0061] (Examples 2 to 5) In the preparation of the base layer forming material, an endless belt was produced in the same manner as in Example 1 except that the blending ratio (parts by mass) described in the table was adopted.
[0062] (Comparative Example 1) <Preparation of base layer forming material> 100 parts by mass of PVdF (NEOFLON VT-100, manufactured by Daikin Industries), 36 parts by mass of c-TiO2 (Titanium Black 13M, manufactured by Mitsubishi Materials Corporation) as a conductive agent, and 400 parts by mass of acetone were kneaded in a ball mill and then stirred to prepare a base layer forming material.
[0063] <Manufacturing of Endless Belt> In the same manner as in Example 1, an endless belt was produced.
[0064] (Comparative Example 2) <Preparation of base layer forming material> In a reaction container equipped with a stirrer, a nitrogen inlet pipe, a thermometer, and a cooling pipe, 44 parts by mass of 4,4'-diphthalic anhydride (BPDA), 40 parts by mass of 4,4'-diaminodiphenyl ether (ODA), and 200 parts by mass of NMP solvent were added, and the mixture was stirred under a nitrogen flow and reacted at a temperature below room temperature (25°C) for about 3 hours, and then the reaction was stopped to prepare a polyamic acid-NMP solution (solid content concentration: 26% by weight) as a precursor of PI. 5 parts by mass of conductive carbon were added to the prepared polyamic acid-NMP solution, mixed with a stirring blade, and then dispersed in a ball mill to prepare a base layer forming material.
[0065] <Manufacturing of Endless Belt> In the same manner as in Example 1, an endless belt was produced.
[0066] (Comparative Examples 3 to 5) In the preparation of the base layer forming material, an endless belt was produced in the same manner as in Example 1 except that the MDI / TODI ratio was changed to the blending ratio (parts by mass) described in the table.
[0067] (Comparative Examples 6 to 8) In the preparation of the base layer forming material, an endless belt was produced in the same manner as in Example 1 except that the flame retardant was changed to the blending ratio (parts by mass) described in the table.
[0068] The materials used are described below.
[0069] ·MDI: "MILLIONATE MT" made by Japan Polyurethane, Mn: 250.26 TODI: "TODI / R203" manufactured by Japan Soda, Mn: 264.29 ·Trimellitic anhydride: aromatic polycarboxylic anhydride, Mn: 192.12 ·4,4'-Diphthalic anhydride (BPDA) ·4,4'-Diaminodiphenyl ether (ODA) Conductive carbon: "Ketjen Black EC300J" manufactured by Lion Specialty Chemicals Flame retardant <1> : Tricresyl phosphate (molecular weight: 368), "TCP" manufactured by Daihachi Chemical Industry Flame retardant <2> : Tolyl di-2,6-xylyl phosphate (molecular weight: 396), "PX110" manufactured by Daihachi Chemical Industry Co., Ltd. Flame retardant <3> : Triphenyl phosphate (molecular weight: 326), "TPP" manufactured by Daihachi Chemical Industry Flame retardant <4> : Cresyl diphenyl phosphate (molecular weight: 340), "CDP" manufactured by Daihachi Chemical Industry Co., Ltd. Flame retardant <5> : Polybrominated biphenyls Flame retardant <6> :Polychlorinated biphenyls Flame retardant <7> :Aluminum hydroxide, "Aluminum hydroxide C-305" manufactured by Sumitomo Chemical Using the produced endless belt, various properties were evaluated according to the following criteria.
[0070] <Tensile elastic modulus> The tensile modulus was measured according to JIS K7127. The tensile speed was 10±2.0 mm per minute. A tensile modulus of 3 GPa or more was marked as "0", and a tensile modulus of less than 3 GPa was marked as "×".
[0071] <Folding resistance (MIT value)> According to JIS P8115, the MIT number of each endless belt was measured under a load of 9.8 N using Folding Endurancetester MIT-D (manufactured by Toyo Seiki Co., Ltd.). The MIT number is an indicator for evaluating folding resistance, and the greater the MIT number, the better the folding resistance. A MIT number of 5K times (5000 times) or more is recorded as "0", and a MIT number of less than 5K times (5000 times) is recorded as "×".
[0072] <Flame retardancy> The flame retardancy evaluation test was performed using the base material of each endless belt in accordance with UL-94. Regarding the evaluation of flame retardancy, "VTM-0" indicates better flame retardancy than "VTM-1". VTM-0 is recorded as "0", VTM-1 is recorded as "△", and VTM-2 and below are recorded as "×".
[0073] <Environmental load> Substances regulated by Rohs REACH (including substances of very high concern) are marked as “×”, and substances not regulated are marked as “0”.
[0074] <Material synthesis time> The synthesis time of polyamide-imide or polyimide was compared. Synthesis time of 15 hours or less was marked as "0", and synthesis time of more than 15 hours was marked as "x".
[0075] <Price> In the synthesis of polyamide-imide, the cost in the case of MDI / TODI=50 / 50 was set to 100, and the relative value was expressed. 120 or less was expressed as "0", more than 120 and 150 or less was expressed as "△", and more than 150 was expressed as "×".
[0076] <Idle rate> The probability of idle rotation of 1 mm or more occurring during initial belt driving was measured using a commercially available MFP unit ("IMC6000" manufactured by Ricoh Corporation). The measurement was performed five times in total using five samples.
[0077]
[0078] In Comparative Example 1, the base layer of the endless belt is made of fluororesin. In Comparative Example 1, although flame retardancy can be ensured, the elastic modulus is low and the material is expensive. Furthermore, there is a problem of environmental load. In Comparative Example 2, the base layer of the endless belt is made of polyimide resin. In Comparative Example 2, flame retardancy can be ensured and the elastic modulus is also high, but the material is expensive, and the manufacturing also requires high temperature and long time, and the productivity is poor, which is disadvantageous in terms of cost.
[0079] In Comparative Example 3, the base layer of the endless belt is composed of polyamide-imide resin, but the isocyanate component is composed of MDI only. Therefore, in Comparative Example 3, the necessary elastic modulus cannot be ensured. In addition, the synthesis time of polyamide imidization becomes long, which is disadvantageous in terms of cost. In Comparative Examples 4 and 5, the base layer of the endless belt is composed of polyamide-imide resin, but the amount of MDI in the isocyanate component is insufficient. Therefore, in Comparative Examples 4 and 5, the folding resistance (MIT number) is poor.
[0080] In Comparative Examples 6 and 7, a halogen compound is used as a flame retardant in the base layer of the endless belt. In Comparative Examples 6 and 7, there are problems in terms of environmental load. In Comparative Example 8, aluminum hydroxide is used as a flame retardant in the base layer of the endless belt. The flame retardant effect of metal hydrate flame retardants is low, so a large amount of addition is required to ensure the necessary flame retardancy. In Comparative Example 8, due to the large amount of addition of the flame retardant, the folding resistance (MIT number) is poor.
[0081] In Examples 1 to 5, the base layer of the endless belt is composed of a polyamide-imide resin, and the MDI / TODI ratio of the isocyanate component is within a specific range. In addition, an organic phosphorus compound is used as a flame retardant. In Examples 1 to 5, the necessary elastic modulus can be ensured, and there is no problem with folding resistance. In addition, the synthesis time of polyamide-imide is also short, and there is no problem in terms of cost. In addition, the environmental load is also taken into consideration. Further, the flame retardancy is also excellent. Therefore, according to the embodiments, it can be seen that both physical properties and flame retardancy are taken into consideration, low cost is achieved, and the environmental load can be taken into consideration.
[0082] Comparison of the examples shows that as the molecular weight of the organic phosphorus compound as the flame retardant increases, the flame retardant is less likely to ooze out to the belt surface, and the occurrence of idling due to a decrease in the friction coefficient is more easily suppressed.
[0083] As mentioned above, although embodiment of this invention is described in detail, this invention is not limited to the said embodiment, Various changes can be made within the range which does not deviate from the summary of this invention.
Claims
1. An endless belt for an electrophotographic device, comprising at least a base layer, wherein: The base layer is formed using a resin composition containing a polyamide-imide resin and a flame retardant, wherein the polyamide-imide resin has a structural unit derived from the following (A) to (C), The molar ratio of the structural unit (α) derived from the (A) to the structural unit (β) derived from the (B) is in the range of (α) / (β)=95 / 5 to 30 / 70, The flame retardant is an organic phosphorus compound, (A) diphenylmethane diisocyanate (MDI), (B) dimethyl diphenyl diisocyanate (TODI), (C) Anhydrides of aromatic polycarboxylic acids.
2. The endless belt for an electrophotographic apparatus according to claim 1, wherein The organic phosphorus compound is an organic phosphorus compound having a molecular weight of 350 or more.
3. The endless belt for an electrophotographic apparatus according to claim 1 or 2, wherein: The anhydride of the aromatic polycarboxylic acid (C) is trimellitic anhydride.
4. The endless belt for an electrophotographic apparatus according to claim 1 or 2, wherein: The organic phosphorus compound is a phosphate ester.
5. The endless belt for an electrophotographic apparatus according to claim 1 or 2, wherein: The content of the organic phosphorus compound is 1.0 part by mass or more and 10 parts by mass or less relative to 100 parts by mass of the polyamide-imide resin.
6. The endless belt for an electrophotographic apparatus according to claim 1, wherein The organic phosphorus compound is an organic phosphorus compound with a molecular weight of 350 or more, The anhydride of the aromatic polycarboxylic acid (C) is trimellitic anhydride, The organophosphorus compound is a phosphate ester, The content of the organic phosphorus compound is 1.0 part by mass or more and 10 parts by mass or less relative to 100 parts by mass of the polyamide-imide resin.
Citation Information
Patent Citations
Endless belt for electrophotographic apparatus
JP2006047587A